Factor affecting employee resist to change in Mara Japan Industrial Institute Beranang / Siti Zulaikha Sudiman and Noor Hazimah Jalaludin - Sudiman, Siti Zulaikha; Jalaludin, Noor Hazimah (2013)
The resistance to change among employee will be reduced in MARA Japan Industrial Institute Beranang in order to obtain the competiveness among the staff. The change will attain the reputation of the organization itself.